2021
DOI: 10.1136/bmjopen-2020-045297
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and views of receiving and delivering information about recovery in acquired neurological conditions: a systematic review of qualitative literature

Abstract: ObjectiveTo review and synthesise qualitative literature relating to the views, perceptions and experiences of patients with acquired neurological conditions and their caregivers about the process of receiving information about recovery; as well as the views and experiences of healthcare professionals involved in delivering this information.DesignSystematic review of qualitative studies.Data sourcesMEDLINE, Embase, AMED, CINAHL, PsycINFO, Web of Science and the Cochrane library were searched from their incepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…In this study, not using a therapeutic method when telling bad news left the women in a state of confusion and shock. In the same context, a systematic review of 30 studies from eight countries indicated that to ensure emotional recovery and improve the experiences of stroke patients and their families, health staff should adopt an approach based on breaking bad news compassionately, and preparing the staff to meet the information needs of patients and their families [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, not using a therapeutic method when telling bad news left the women in a state of confusion and shock. In the same context, a systematic review of 30 studies from eight countries indicated that to ensure emotional recovery and improve the experiences of stroke patients and their families, health staff should adopt an approach based on breaking bad news compassionately, and preparing the staff to meet the information needs of patients and their families [11].…”
Section: Discussionmentioning
confidence: 99%
“…Some participants indicated that the pain affected their mood and socialization with others. Participant woman (11) said: "I quickly became angry because of the pain, when the pain and numbness started on the left side of my body, I lost control of my mood, and I don't want to deal with anyone. "…”
Section: Experiencing Intolerable Painmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the professional must know how to convey the information, providing information about the disease, and conveying words of encouragement in the message [ 41 ]. In the systematic review by Burton et al [ 42 ] regarding the experiences of patients with acquired neurological conditions and their caregivers about the process of receiving information about recovery, the importance of providing the right information at the right time is described, together with managing expectations and the way in which the message is given, learning to talk about recovery, and managing emotions in an uncertain context such as the recovery of acquired neurological processes. Communication between the stroke patient and healthcare professionals helps to adjust patients’ expectations towards recovery during rehabilitation [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…He commits to thoughtful consideration of the patient’s previous experiences, current stressors, and potential desire for social supports during conversations. He will elicit and honor the patient’s preferences for type and amount of information discussed and allow the patient opportunities to initiate conversations based upon his desire for information 29,30 . See SDC Appendix 2 (Supplemental Digital Content 2, http://links.lww.com/PHM/B594) for an approach to spinal cord injury prognosis disclosure and palliative care communication skills relevant to setting goals.…”
Section: Case 2: Palliative Communication Skills In the Inpatient Reh...mentioning
confidence: 99%